PPKM DAN KOLAPSNYA SEKTOR INFORMAL: DILEMATISNYA PERTUMBUHAN EKONOMI DI INDONESIA - Mukti Diapepin (UIN Imam Bonjol Padang, 2021)
Covid-19 has been infecting the world for almost two years and Indonesia, in particular. Along with the spread of the new Delta variant, it has triggered its spread in Java and Bali. Not including the death rate which continues to increase from time to time. This paper utilizes qualitative methods in working on the written data obtained. The government through the PPKM policy strives to maintain to reduce the number of transmission and death through restrictions on movement space. However, in the midst of policies and social assistance disbursement of up to trillions, apparently it has not been able to guarantee the survival of the informal sector. The sector, which mostly depends on the interaction of buyers and service users, is the most vulnerable when dealing with PPKM.